Studies On In Vitro Colonization, Karyomorphology, And Temephos Susceptibility Of Simulium Damnosum Theobald Complex. - Osei-Atweneboana, M.Y. (University of Ghana, 1996)
The strategy of using insecticides against Simulium damnosum s.I. vectors, adopted by Control Programmes for human onchocerciasis in West Africa has led to increased vector biology studies and has at the same time also revealed the paucity of our knowledge in this area to effectively control the vectors means that laboratory colonies need to be established to enable experiments to be carried out. It also means there is a need to intensify research on aspects of the biology that determine the epidemiological importance of the various species. For the first part of the present study, a simple but effective technique was developed and used in various ways, including simulated group oviposition, to study in vitro oviposition of female flies. It was found that using a dripping effect of water was an improvement over the water immersion method that was used by most researchers. For the second part of the study, cytotaxonomic studies for species distribution and/ for the revision of S. sanctipauli s.I. populations from the major river systems in South West Ghana, were carried out. Two different populations of S. sanctipauli s.s were recognized with a newly identified inversion that occurred in the R. Tano populations which is named inversion IS-25. For the final part of the study, tests were carried out on S. sanctipauli s.s. populations from two sites on the Rivers Pra and Tano, with the aim of relating chromosomal inversions to Temephos (an organophosphate insecticide) susceptibility levels. It was found that S. sanctipauli s.s. populations from Sutri rapids (R.Tano) were resistant to Temephos, whilst those from Sekyere-Heman (R. Pra) were susceptible at the recommended diagnostic dose. A chromosomal analysis however, did not show the presence of any unique inversion or differences in the chromosomal inversion frequencies between the general populations and the resistant population. Therefore it was concluded that no chromosomal inversions were responsible for the resistance that was detected on the R. Tano.